Modelagem da emissão de respostas pré-correntes em situações de resolução de problemas em crianças de 7 e 8 anos de idade: uma adaptação do Thinking Aloud Pair Problem Solving (TAPPS) - Manpetit, Tereza Attem Felix Santos (2019)
This research aimed to replicate part of Bitencourt’s (2009) procedures, in order to investigate the effects of the acquisition of preliminary behaviors in one specific problem on the behaviors exhibited in the resolution of another problem, in which those preliminary behaviors would be theoretically effective. A version of the Thinking Aloud Pair Problem Solving (TAPPS) was applied in order to evaluate its effectiveness in increasing the use of heuristic rules with new problems and reducing attempts under S-delta control, as well as to evaluate if the increase of correct answers of the participants in one game made them more efficient in other game. The research took place in a school in the city of São Paulo, Brazil, with eight participants from seven to eight years old and the games Cara a Cara (Face to Face) and Jogos Boole (Boolean Games). A pre-test was performed to evaluate the children’s individual repertoire in situations that were similar to those of the experimental procedure, which consisted of three problem-solving situations. During the Intervention Phase, the participants were divided into two groups of four members each. Group 1 started by playing five matches of the Boolean Games and then moved on to three Face-to-Face matches. For Group 2, the presentation order of the games was inverse. The participants were submitted to a post-test, which also consisted of three problem-solving situations, as difficult as the pre-test ones. The results indicated that the participants of both groups decreased the number of heuristic and non-heuristic responses during the games, with very similar performance, and that the number of matches performed by the children was insufficient to identify possible influences regarding the different orders that the games were presented. However, the decrease in the emission of non-heuristic responses demonstrated that TAPPS might be effective in increasing participants’ problemsolving repertoire